Pengembangan Material Maju Superkonduktor Mg-B dengan Penambahan Graphene Oxide melalui Proses Powder in Sealed Tube - Mahendra, Brillian Ardy; Herbirowo, Satrio; Saefuloh, Iman; Handayani, Murni (Universitas Nusantara PGRI Kediri, 2022)
MgB2 is a high possible superconducting material that can be applied quite practically with the functionalization of Mg-B materials. Material development is carried out by adding carbon, namely Graphene Oxide (GO), which is a single atom layered material. The Powder in Sealed Tube (PIST) method is practically used to reduce oxidation. This study aims to analyze the effect of GO material doped with the PIST method made from MgB2 with a sintering temperature of 800℃ for 2 hours on its superconductivity, compound formation, and microstructure. The manufacturing process is carried out in a 1:2 ratio where 98% purity Mg is mixed with Boron, which is then added with 0, 0.3 and 3% wt GO doping, all ingredients are mixed stoichiometrically. The material that has been put in a tube and compacted sufficiently into SS316L which has been closed on one side to enter the powder, is then compacted with high pressure up to 1000 MPa. The material is sintered at a temperature of 800℃ for 2 hours which is then carried out by cooling in the furnace and taking bulk samples. The XRD results showed the formation of the dominant MgB2 phase and the formation of an impurity phase in the form of MgO and obtained a decent crystal size of 295 which was owned by the 3%wt GO PIST MgB2 sample. The SEM test shows the forms of formation (agglomeration) in each sample, with the presence of several axes. Cryogenic testing shows that with doping there is a movement of critical temperature to a lower direction where MgB2 0%wt GO has a TcOnset value of 39.4 K and a TcZero of 38.7 K, while MgB2 3%wt GO has a TcOnset value of 39.6 K and TcZero of 38 K.